2002
DOI: 10.1089/105072502760043512
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Cardiovascular Disease in Women with Subclinical Hypothyroidism

Abstract: Overt hypothyroidism may result in accelerated atherosclerosis and coronary heart disease (CHD) presumably because of the associated hypertension, hypercholesterolemia, and hyperhomocysteinemia. As many as 10%-15% of older women have subclinical hypothyroidism (SH) and thyroid autoimmunity. Whether SH is associated with risk for CHD is controversial. We examined 57 women with SH and 34 healthy controls. SH was defined as an elevated thyrotropin (TSH) (>4.5 mU/L) and normal free thyroxine (FT(4)) level (8.7-22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
143
6
16

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(183 citation statements)
references
References 37 publications
18
143
6
16
Order By: Relevance
“…This finding is partially consistent with findings of Busselton Thyroid Study, which concluded that subclinical hypothyroidism is not associated with hypertension [19]. However, in another study on women, subclinical hypothyroidism was found to be associated with diastolic hypertension, hypertriglyceridemia, and increase in BMI [26]. In our study, we did find higher TSH level to be associated with presence of hyperlipidemia in the patients; however, this association was not statistically significant ( p  = .076).…”
Section: Discussionsupporting
confidence: 88%
“…This finding is partially consistent with findings of Busselton Thyroid Study, which concluded that subclinical hypothyroidism is not associated with hypertension [19]. However, in another study on women, subclinical hypothyroidism was found to be associated with diastolic hypertension, hypertriglyceridemia, and increase in BMI [26]. In our study, we did find higher TSH level to be associated with presence of hyperlipidemia in the patients; however, this association was not statistically significant ( p  = .076).…”
Section: Discussionsupporting
confidence: 88%
“…SCH is defined as a mild elevation of TSH and normal levels of free thyroid hormones. The association between SCH and individual cardiovascular risk factors has also been explored, with discordant results (4)(5)(6). Even more controversial is the association between SCH and insulin resistance (7).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidences indicate that subclinical hypothyroidism is also related to dyslipidemia and T4 treatment of this condition may improve the lipid profile of the patients [11,12]. Consequently, subclinical hypothyroidism is associated with an increased risk of coronary heart disease [13,14] and with increased coronary heart disease events and cardiovascular deaths [15].…”
mentioning
confidence: 99%